It Is A Satisfaction To Take Care Of My Grandchildren: Informal Care Of Cucu Amongmalay Grandmothers In Kuching - Jamayah, Saili; Edris, Aden; Siti Norazilah, Mohd Said; Nor Hasniah, Ibrahim (Institute of Borneo Studies, UNIMAS, 2016)
Despite the relatively high degree of research in formal care settings or licensed services, there remains lack of research on issues faced by the informal care providers. Grandparents are by far the greatest providers of informal child care, yet little is known about their experiences or factor associated with this type of care and its implications. The rise in the number of maternal employment is seen as being among the most significant changes to have affected family organisation. There are several popular assumptions that may be held by general public: that grandmothers are overburden and stress looking after their cucu. This study sought to determine the profile and the prevalence of grandmothers providing extensive care for grandchildren. Using a sample of three grandmothers aged 58, 62 and 65 years old, this paper explores the voices of grandmothers in taking care of their grandchildren. This paper thus highlights some of the experiences of the grandmothers including the thoughts of the descendents, the rewarding side and the roles and expectations. As the informal care by grandparents is increasingly popular, the research outcomes will have important implications to the extant literature on grandparents taking care of their grandchildren.